Modelling the effects of textile preform architecture on permeability - Wong, Chee Chiew (2006)
Liquid Composite Moulding (LCM) processes are identified as one of the most potentially advantageous manufacturing routes. The challenge currently is to increase their reliability and expand their applicability. To that end, it was perceived that there was a lack of an advanced integrated simulation tool for the manufacture of three-dimensional, multi-layer textile composites. The tools for the analyses of fabric forming and subsequent flow during LCM processes were simple and immature, with the latter suitable to describe flow in thin structures only. Another noted deficiency was that the simulations provided a single answer to any given problem. Industrial experience has shown that during mould filling, due to the nature of statistical variation in the material properties, the filling patterns and arising cycle times are rarely the same between a given set of identical mouldings.